2002
DOI: 10.1093/toxsci/69.2.344
|View full text |Cite
|
Sign up to set email alerts
|

Antiandrogenic Effects in Vitro and in Vivo of the Fungicide Prochloraz

Abstract: The commonly used imidazole fungicide prochloraz was tested for antiandrogenic effects in vitro and in vivo. Prochloraz, but not the metabolites 2,4,6-trichlorophenoxyacetic acid or 2,4,6-trichlorophenol, inhibited the R1881-induced response in an androgen receptor reporter gene assay. In the Hershberger assay, prochloraz exposure at all dose levels (50, 100, and 200 mg/kg) given orally to castrated testosterone (T)-treated males markedly reduced weights of ventral prostate, seminal vesicles, musc. levator ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
89
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(97 citation statements)
references
References 45 publications
6
89
2
Order By: Relevance
“…1) out of a total of several thousand diseases. These predictions for effects of prochloraz on human health are in line with experimental data from rats indicating that the main adverse outcomes after exposure to prochloraz are diseases related to reproductive health [35][36][37][38]. Another pesticide, mancozeb, underwent the same network analysis and was found to be associated with, for example, inflammatory targets and had no targets in common with prochloraz or other tested pesticides [20].…”
Section: A Case Study: Computational Systems Biology Applied On Prochsupporting
confidence: 77%
See 1 more Smart Citation
“…1) out of a total of several thousand diseases. These predictions for effects of prochloraz on human health are in line with experimental data from rats indicating that the main adverse outcomes after exposure to prochloraz are diseases related to reproductive health [35][36][37][38]. Another pesticide, mancozeb, underwent the same network analysis and was found to be associated with, for example, inflammatory targets and had no targets in common with prochloraz or other tested pesticides [20].…”
Section: A Case Study: Computational Systems Biology Applied On Prochsupporting
confidence: 77%
“…Prochloraz is a widely used pesticide that has been demonstrated to have endocrine activity. In animals, it has been shown to cause adverse reproductive outcomes in the male offspring after exposure during foetal life [35][36][37][38]. Prochloraz is known to demasculinize male rat foetuses and virilize female foetuses; however, as clinical studies of environmental chemicals are not carried out, little is known about human effects of this compound.…”
Section: A Case Study: Computational Systems Biology Applied On Prochmentioning
confidence: 99%
“…For example, studies have shown that the fungicide effectively inhibits aromatase (CYP19) activity in both fish and mammals, blocking the conversion of testosterone (T) to 17b-estradiol (E2) and acting in vivo as an antiestrogen (Ankley et al, 2005;Mason et al, 1987;Sanderson et al, 2002;Thorpe et al, 2007;Vinggaard et al, 2000). Prochloraz also can cause antiandrogenic effects in vertebrates either through direct antagonism of the androgen receptor or through inhibition of cytochrome P450 c17a-hydroxylase/17,20-lyase (CYP17), a steroidogenic enzyme involved in T production (Blystone et al, 2007;Noriega et al, 2005;Vinggaard et al, 2002Vinggaard et al, , 2005. Due to its varied effects on the vertebrate hypothalamic-pituitary-gonadal (HPG) axis, prochloraz has been used as a model compound for studies focused on different mechanisms of endocrine disruption (Gray et al, 2006;USEPA, 2007).…”
mentioning
confidence: 99%
“…This could be in response to decreased T in the males (Villeneuve et al, 2007b), or it might be indicative of adaptation to a different mechanism of action of prochloraz. Specifically, in addition to inhibiting CYPs, it has been proposed that prochloraz can affect the vertebrate endocrine system through direct antagonism of the AR (Vinggaard et al, 2002(Vinggaard et al, , 2005; as such, upregulation of the gene coding for the receptor could be viewed as adaptive. Zhang et al (2008) used QPCR to examine expression of a number of the same genes we evaluated in various tissues from male and female Japanese medaka exposed to prochloraz.…”
mentioning
confidence: 99%
“…In these studies, androgen action in utero, or on pubertal development were examined Owens et al 2007). Recognized antiandrogens fell into classes including dicarboximide (Gray et al 1994;Kelce & Wilson 1997) and imidazole fungicides (Vinggaard et al 2002;Noriega et al 2005), organochlorine insecticides (Kelce et al 1995), urea-based herbicides (Gray et al 1999;Lambright et al 2000), phthalate esters used as plasticizers (Parks et al 2000;Howdeshell et al 2007), and polybrominated diphenyl ethers (PBDEs) used as flame retardants (Stoker et al 2005). Natural hormones (Stumm-Zollinger & Fair 1965) and birth control agents (Tabak et al 1981) occurring in wastewater prompted concern over sewage effluents.…”
Section: The "Endocrine Disruptor" Hypothesismentioning
confidence: 99%